Thermodynamic analysis of r134a in an organic rankine cycle for power generation from low temperature sources (2014)
This paper reports the main results of a thermodynamic study realized on the use of a low temperature heat source (150ºC as maximum) for power generation through a subcritical Rankine power cycle with R134a as working fluid. The procedure for analyzing the behavior of the proposed cycle consisted of modifying the input pressure, temperature and/or discharge pressure of the turbine with working fluid at conditions of both saturation and overheating. Results show that the efficiency of the cycle for this fluid is a weak function of temperature, i.e., overheating the inlet fluid to the turbine does not cause a significant change in the efficiency. However, when the pressure ratio in the turbine increases, it is much more efficient, and also, as the input temperature to the turbine rises, the efficiency increases more sharply. Furthermore, the effect of adding an internal heat exchanger to the cycle was analyzed, giving as a result a maximum efficiency of 11% and 14% for the basic cycle and with an internal heat exchanger, respectively.